(untitled) (Emergency Care Journal, 2020)
Over a billion Peripheral Intra-Venous Cannulas (PIVC) are used globally every year with at least 25 million sold annually in the UK.1,2 The NHS spends an estimated £29m of its annual acute sector budget on PIVC procurement3 and around 70% of all hospitalised patients require at least one PIVC during their stay.4 Despite their extensive and routine use, PIVC failure rates are reported as high as 50-69%.5-7 In addition, many PIVCs remain unused following insertion, particularly in the Emergency Department (ED).8,9 The risk factors for PIVC failure are not well understood and the literature has found extensive regional variation in practice when it comes to PIVC insertion and management.1,7,10 While various technologies have been developed to address these issues, there remains a need for standardised, evidence-based guidelines.